(3eNJUQ ZfjI GdeJedj TQM efjI GdeUdjs - (3GdMdHj, EHQGgje Hf eMeO EHQGgje, J (B956 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj LYd GdYHGOI eaJGM GdSYGOI CeG HYO ajbhd EHQGgje Hf eMeO Hf EHQGgje GdMdHj bO cfJ TQMJ cJGH efjI GdeUdj TQMG hSejJg HZfjI GdeJedj dcf QCjJ ajg HYV GdEWGdI aCMHHJ Cf CNJUQ ef aQGFO OdGFdgs
(3BNQgG (B:s
(3bGd Gddg JYGdi hCeQ Cgdc HGdUdGI hGUWHQ YdjgG dG fSCdc QRbG fMf fQRbc hGdYGbHI ddJbhis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 66s
(3eYLe GdeDdajf (B1 / 55s
(3cTa GdXfhf (B2 / 1887s
(3TPQGJ GdPgH (B8 / 308s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs